Pengembangan Model Prediksi Penjualan Ice Cream UMKM Jogja Menggunakan Metode Autoregressive - Muhammad Rais Ramadhani; Nurmalitasari; Nurchim (Pendidikan Matematika Universitas PGRI Yogyakarta, 2024)
There are Micro Small Medium Enterprises (MSMEs) Jogja is included in the new category because of its launch in early 2023, but it already has a total turnover of hundreds of millions. This MSME focuses on enlisted Ice Cream sales with dozens of Ice Cream menu variants. The unstable level of sales originating from trends or seasons becomes a separate enemy for business actors. This study aims to carry out the permanent sales of MSME Jogja using the autoregressive method. The steps taken are (1) data collection, (2) Calculation of ACF and PACF, (3) data processing, and (4) calculation of error values. The data used in the current study is the 8 -8-month sales transaction data. The results showed that the autoregressive method can predict the sale of MSME Jogja with a low error value of MAE = 0.18 and RMSE = 0.14. With this, Ice Cream sales predictions using the Autoregressive Method can be accepted, which results in sales predictions in the following month, May 2024, as many as 1,118 products were sold. Suggestions for further researchers to research each existing menu variant. Keywords: Prediction, Sales, Ice Cream, Autoregressive